Cross-domain analysis of YOLOv8 and faster R-CNN models for enhanced precision in maritime object detection - Zainal Abidin, Zulkifli; Norazaruddin, Muhammad Aiman; Tengku Anuar, Tengku Aizat (Taylor’s University, 2025)
Recent advancements in machine vision, particularly through Convolutional Neural Networks (CNNs), have significantly improved object detection in maritime environments. This study evaluates the performance of two leading object detection algorithms—YOLOv8 and Faster R-CNN—along with their respective variants, across two specialized maritime datasets: SeaShip and the Sea Maritime Dataset (SMD).